Synthesis of Polymer Electrolyte Membrane based on Acid-Base complex pair and Its Characteristics - Irfan Gustian; Sevim Ãœnugur Ã‡elik; Ahmad Zainuddin; Wawang Suratno; Ayhan Bozkurt; Rustam Efendi Siregar (Institute for Research and Community Services (LPPM) ITB, 2014)
In this work, acid-base complex pair polymer electrolyte membranes on sulfonated polysulfone with 1H-benzotriazole were investigated. Polysulfone was sulfonated in 1,2-dichloroethane using the homogeneous method with trimethylsilyl chlorosulfonate as sulfonating agent. The monomer mole ratio between polysulfone and trimethysilyl chlorosulfonate was 1:1.5.The sulfonated polysulfone was added with 1H-benzotriazole at mole ratios of x = 0.5 and x =1. The proton transfer from 1H-benzotriazole to the sulfonated polysulfone was measured using FTIR. Thermo-gravimetry analysis showed that the samples were thermally stable up to approximately 250°C and the maximum proton conductivity was found to be 3.34 x 10-4 S cm-1 at 150°C.